(untitled) (African Journal of Biomedical Research, 2020)
The aim of the study was to create the need for awareness of dental check-up; and to access the value for aesthetic dental restoration. A descriptive cross-sectional study was done with the use of self-administered questioners designed in a clear message expressed in English language including 20 questions were distributed to undergraduate age range 16-30 years in the University of Ibadan. A total of 417 students responded to the questionnaire of which 92.1% are aware about dental check-up, 46.8% have had pain and discomfort from tooth,19% have tooth fracture, 20% have tooth discolouration, 27% have visited a dentist, 2.9% have a tooth coloured filling,7% are wearing removable denture .The result of this study shows an awareness of dental check-up and reduced value of aesthetic restoration among undergraduate students in the University of Ibadan. The study shows that despite being aware about dental check-uap and having oral health problems this did not increase the practice of dental visit or increase in the value of aesthetic restoration among the University of Ibadan undergraduates